Corrosion inhibition efficiency of steel by mango peel extract in hydrochloric acid at different temperature / Nur Aina Radin Sukimi ... [et al.] - Radin Sukimi, Nur Aina; Yahya, Solhan; Alias, Nurul Zawani; Shamsudin, Shaiful Rizam; Ahmad, Zuliahani; Din Yati, Mohd Subhi (Research Management Institute (RMI), 2023)
Nowadays, researchers are interested in exploring the possibility of replacing harmful inorganic chemicals with green organic substances derived from natural sources. This study focuses on accessing the potential of a green corrosion inhibitor for mild steel, using plant extracts from local mango peel. The Harumanis mango peel leftover was extracted using solvent extraction techniques and the chemical compounds were characterized through Fourier Transform Infra-Red (FTIR) and UV-visible spectroscopy. The analysis showed that the crude extract of Harumanis mango peel (HMPE) contained active functional groups for corrosion inhibitory properties such as -OH, -COOH, -C=O and aromatic ring structure. The presence of mangiferin and other flavonols, likely acid gallic, was also detected. The efficiency of HMPE as a corrosion inhibitor for mild steel was investigated through a conventional corrosion test. The immersion test was carried out in different temperatures at 30, 40, 50 and 60 ⁰C with and without the addition of the 50 to 350 ppm HMPE inhibitor in 1 M hydrochloric acid, HCl. The result showed that the corrosion inhibition efficiency for mild steel in acidic medium increased as the concentration of the Harumanis mango peel increased.